The Effects Of Integrated Journal Discussion Board (Ijdb) On Students’ Motivational Beliefs And Self-Regulated Learning Strategies In Higher Education - Fung, Chorng Yuan (2018)
Higher education is a platform to cultivate students to be lifelong learners. Students are expected to set their own learning goals, select suitable learning strategies, self-monitor and evaluation their learning outcome. However, many students in higher education are not prepared to adapt to such student-centred approach of learning. Hence, effective intervention is needed to improve students’ self-regulated learning skills. This study investigated the effect of Integrated Journal Discussion Board (IJDB) on students’ motivational beliefs and use of Self-Regulated Learning (SRL) strategies in higher education. These are essential variables of student-centred approach of learning. IJDB was a tool situated in the Learning Management System (LMS) university which is known as Blackboard Learn. It involved the use of e-Learning Journal and Asynchronous Discussion Board (ADB) in integration. This study used a mixed method approach. Fifty-four students have taken the pre-test and post-test using Motivated Strategies for Learning Questionnaire (MSLQ). Time series data on motivational beliefs and SRL strategies were collected over the intervention period. The changes in the pre-test post-test scores were analysed using paired t-test while the changes in the time series were analysed using repeated measures Analysis of Variance (ANOVA). In addition, time series graphs were used to identify the trends in the time series data. The results of pre-test post-test analysis and time series data revealed that there was a significant increase in the motivational beliefs and SRL strategies use over the intervention period.